Specific immune response in the respiratory tract after administration of an oral polyvalent bacterial vaccine. - Clancy, R L (1983)
An oral killed polyvalent bacterial vaccine was assessed in a double-blind trial involving healthy volunteers. Three courses of oral vaccine were given over a 2-month period; each course contained 10(10) Haemophilus influenzae and 7 X 10(9) Staphylococcus aureus organisms. Immunity was assessed by monitoring antibody in saliva and serum over a 3-month period. No evidence of a nonspecific effect on immune parameters (immunoglobulin levels and Escherichia coli antibody) was detected in saliva or serum. An increase in H. influenzae antibody in saliva was detected in 55% of subjects receiving the vaccine compared with 6.7% of the placebo group. Antibody was associated with immunoglobulin A (IgA), IgG, and IgM, but the greatest increases over preimmunization levels were detected in the IgA class. No increase in serum antibody levels was detected. Subjects with higher preimmunization levels of salivary antibody to H. influenzae were less likely to respond to the oral bacterial vaccine. No increase in S. aureus antibody was detected in saliva or serum.